2017
DOI: 10.1016/j.metabol.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Acute low-dose endotoxin treatment results in improved whole-body glucose homeostasis in mice

Abstract: Background Obese individuals present with an increased inflammatory tone as compared to healthy, normal-weight individuals, which is associated with insulin resistance. One factor hypothesized to contribute to increased inflammation in obese and diabetic states is elevated blood endotoxin levels, a condition known as metabolic endotoxemia. In non-obese and insulin sensitive individuals, circulating endotoxin concentrations fluctuate over the course of the day with elevations in the post-prandial state that ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
3
0
2
Order By: Relevance
“…Co-administration of the anti-inflammatory resveratrol, restored normal insulinogenic index, suggesting inflammation of insulin-dependent organs to be the cause of LPS-mediated impaired glucose homeostasis [120]. However, Stevens et al demonstrated that an acute low-dose LPS (0.1 µg/kg) had a positive impact in glucose tolerance in C57BL/6N mice, but without increasing glucose uptake [121]. Thus, for further accuracy, it is important to reflect on the definition of high and low LPS dosages.…”
Section: ) the Involvement Of Gut Dysbiosis And Endotoxemia In At Dys...mentioning
confidence: 99%
See 1 more Smart Citation
“…Co-administration of the anti-inflammatory resveratrol, restored normal insulinogenic index, suggesting inflammation of insulin-dependent organs to be the cause of LPS-mediated impaired glucose homeostasis [120]. However, Stevens et al demonstrated that an acute low-dose LPS (0.1 µg/kg) had a positive impact in glucose tolerance in C57BL/6N mice, but without increasing glucose uptake [121]. Thus, for further accuracy, it is important to reflect on the definition of high and low LPS dosages.…”
Section: ) the Involvement Of Gut Dysbiosis And Endotoxemia In At Dys...mentioning
confidence: 99%
“…However, Stevens et al . demonstrated that an acute low-dose LPS (0.1 µg/kg) had a positive impact in glucose tolerance in C57BL/6N mice, but without increasing glucose uptake [ 121 ]. Thus, for further accuracy, it is important to reflect on the definition of high and low LPS dosages.…”
Section: Introductionmentioning
confidence: 99%
“…However, while the immune system responds to the pathogenic threat, other physiological parameters, such as body temperature (Skold-Chiriac et al, 2015), are shifted from their typical homeostatic range to varying degrees. As such, immune system activation frequently results in changes to metabolism-associated metrics, including metabolic rate (Ardia et al, 2012;Martin et al, 2003), food consumption rate (Skold-Chiriac et al, 2015) and circulating nutrient levels (Stevens et al, 2017). Thus, while initiating an immune response allows the individual to eliminate or ameliorate an immunological threat, mounting an immune response also perturbs other physiological systems away from their typical homeostatic ranges.…”
Section: Introductionmentioning
confidence: 99%
“…O aumento de citocinas e fatores pró inflamatórios, como aumento de expressão de IL1-β e IL-6 em micróglia (Zhang et al, 2017) e aumento de expressão de TNFα e IL-6 em fígado de camundongos (Stevens et al, 2017) em resposta ao LPS tem sido mostrado na literatura. A inflamação de baixo grau induzida por ácido graxo saturado, principalmente o palmitato também é confirmada por diversos estudos que mostram um aumento da expressão de IL-6, TNF-α, NFkB, pJNK e IkBα em células embrionárias de hipotálamo, micróglia e hepatócitos de camundongos (Andersson e Tracey, 2012b;Dalvi et al, 2017;Ji et al, 2018).…”
Section: ™]) Primeiramente Avaliamos Se Esta Linhagem Expressava O Re...unclassified
“…Stevens e colaboradores demostraram aumento da fosforilação da proteína AKT e IRS-1 em resposta ao estímulo com LPS em células do músculo esquelético. Os resultados mostraram ainda o aumento da síntese de glicogênio nessas células em resposta ao desafio com LPS, embora não observaram diferenças na expressão de PEPCK(Stevens et al, 2017). CRL…”
unclassified